Childhood, Adolescents, and Young Adults (?25 y) Colorectal Cancer: Study of Anatolian Society of Medical Oncology - Kaplan, Muhammet A.; Isikdogan, Abdurrahman; Gumus, Mahmut; Arslan, Ulku Y.; Geredeli, Caglayan; Ozdemir, Nuriye; Yildiz, Ramazan (Lippincott Williams & Wilkins, 2013)
Purpose: To evaluate the clinicopathologic characteristics and treatment outcomes of young patients with colorectal cancer (CRC). Methods: Between May 2003 and June 2010, 76 patients were found eligible for this retrospective study. Age, sex, presenting symptoms, patients with acute presentation, family history, presence of polyps, histologic features, localization and stage of the tumor, treatment outcomes, time and site of recurrence, sites of metastasis, and survival outcomes were recorded from the patient files. Results: Seventy-six patients (55.3% male) with a median age of 23 years were evaluated. Patients were evaluated in 2 groups as follows: child-adolescent (0 to 19 y, n=20) and young adult (20 to 25 y, n=56). Sex and symptoms (abdominal pain and rectal bleeding) were significantly differed between the groups and acute presentation was close to statistical significance. Overall survival significantly increased in patients undergoing curative surgery (P<0.001). Other parameters affecting the survival was stage of disease (P=0.004). Response to palliative chemotherapy in metastatic patients (P=0.042) and postoperative adjuvant chemotherapy had a statistically significant survival advantage (P=0.028). Conclusions: Diagnosis of CRC should not be excluded solely on the basis of age. CRC features in young-adult patients are more similar to adults compared with that of child-adolescent patients according to the symptoms and presentation. In patients with CRC in this age group, curative surgery, adjuvant chemotherapy, and palliative chemotherapy provide survival advantage.
Keywords: colorectal cancer; young; adolescent; childhood